THE EFFECT OF DIFFERENTIATION LEARNING USING THE PHET VIRTUAL LABORATORY ON STUDENTS' CRITICAL THINGKING SKILLS - Fuzna Laela; Norma Bastian; Rinto Rinto (Universitas Muhammadiyah Cirebon, 2024)
This research aims to determine the effect of differentiated learning using the PhET virtual laboratory on students' critical thingking skills in vibration and waves. This research uses quantitative experimental research methods with a non-equivalent control group design. This research used two classes with a sample size of 40, consisting of 20 experimental class students and 20 control class students. The instruments used for differentiated learning are diagnostic assessments and formative assessments. Meanwhile, the critical thingking skills test instrument consists of 20 pretest and posttest questions. Data were processed statistically non-parametrically using the Wilcoxon Test and N-Gain Test. The results of the research show that there is an influence of differentiated learning using the PhET virtual laboratory on students' critical thinking skills in vibration and waves as evidenced by the Asmp value. Sig 0.000. No students experienced a decrease in learning outcomes and experienced an increase of 30%. The effectiveness of differentiated learning that is applied has an effect of 61% in the